PERAN FOOD AND AGRICULTURE ORGANIZATION (FAO) DALAM UPAYA MENGATASI KRISIS PANGAN DI UKRAINA TAHUN 2022-2023 - Salsabilla, Aura; Saeri, Mohammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study examines the role of the Food and Agriculture Organization (FAO) in addressing the food crisis in Ukraine during 2022–2023, triggered by the armed conflict between Russia and Ukraine on February 24, 2022. In 2022, Ukraine became the center of attention when a hunger crisis began to hit due to the prolonged conflict, especially due to the impact of the Russia-Ukraine war. This condition was exacerbated by disruptions to the food supply chain, displacement of residents, and significant damage to agricultural infrastructure. This crisis put millions of people in Ukraine at risk of acute hunger, especially vulnerable groups such as children, pregnant women, and the elderly. The theoretical approach used is Clive Archer's theory regarding the role of international organizations as actors. This study uses a qualitative method with a literature study technique obtained through the official FAO website, books, journals and official documents. The results of the study show that FAO acts as an independent actor that designs interventions such as the Rapid Response Plan, Ukraine Response Program and provides special post-war training to farmers in Ukraine. This role shows that FAO not only carries out technical tasks, but also plays a strategic role in global food governance. This study concludes that FAO is an international organization that plays an active and complex role in responding to cross-border humanitarian crises. Keywords: FAO, food crisis, Ukraine, international organizations